Gender, agriculture policies and climate smart agriculture in India - Barooah, Prapti; Alvi, Muzna; Ringler, Claudia; Pathak, Vishal (International Food Policy Research Institute, 2022)
India’s agricultural systems are increasingly affected by the adverse effects of climate change. While the Government of India has put together an impressive set of programs to address climate change impacts on agriculture, substantial shortcomings of these programs have been identified, especially in reaching women farmers. Women’s increased vulnerability to climate change and reduced access to climate smart agricultural practices can be attributed to limited land ownership, poor access to credit, reduced access to information and formal extension, and time pressures from multiple domestic and productive demands on their time. We undertake an extensive policy review of India’s agriculture and climate policies and program, and supplement that with a series of focus group discussions with women and men farmers in Gujarat to discuss constraints and potential entry points for better reaching women farmers with climate smart agriculture practices. Village cooperatives and self-help groups can be key intermediary organizations that can support women’s access at the local, state and country level.